Protective effects of methylprednisolone in kidney: aortic occlusion-reperfusion model in rats - Seçici, Serkan; Özsin, Kadir Kaan; Özyiğit, M.özgür; Arda, Omer; Üstündağ, Yasemin (The European Research Journal, 2023)
Objectives: Ischemia/reperfusion (I/R) injury is commonly seen in cardiovascular surgery, activates inflammation and causes renal damage. In this experimental study, we aimed to assess the effects of different doses (5 and 30 mg/kg) of methylprednisolone (MP), which has anti-inflammatory effect, on renal ischemia/reperfusion (I/R) injury. Methods: Thirty-two male Wistar albino rats were randomly divided into four groups (n = 8). The sham group underwent midline laparotomy and dissection of the abdominal aorta without occlusion while the I/R group underwent suprarenal aortic ischemia for 45 minutes followed by 180 minutes of reperfusion. In the 5 mg/kg MP and 30 mg/kg MP groups, MP was administered intraperitoneally. At the end of the experiment, blood samples were obtained, and kidneys were extracted. Results: Pretreatment with methylprednisolone did not influence serum BUN and creatinine levels. Serum TNF-α levels and ischemia-modified albumin levels were significantly lower in the MP groups compared to the I/R group (p < 0.05). Histological examination demonstrated severe injury in the I/R group and treatment with MP attenuated the severity. The difference was significant in doses of 30 mg/kg MP. Conclusions: This results of the model of renal I/R injury presented in this work reveal the anti-inflammatory and the protective effects of MP in cases of renal I/R.